2009
DOI: 10.2135/cropsci2008.06.0330
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of a Forage Bermudagrass Core Collection

Abstract: Bermudagrass (Cynodon sp.) is an important warm‐season forage grass for the South and may have value as a bioenergy feedstock. The objective of this study was to measure the genetic relatedness among entries of the Cynodon clonal forage bermudagrass core collection and seven commercial forage cultivars using plant phenotype and molecular marker data from amplified fragment length polymorphisms. The collection was assessed for 22 phenotypic traits, including forage quality, plant architecture, growth habit, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Fifty entries with the widest range in rumen digestibility and fiber were selected for the current study (Table 1). The Table 1 Bermuda grass entries and their ranking for high (H), medium (M), or low (L) levels of IVDMD, NDF, ADF, ADL from previous screening, leaf/stem coarseness, and genetic clustering from breeder plots and the Bermuda grass core collection grown at Tifton, GA molecular genetic relationship between these entries was documented using amplified fragment-length polymorphisms (AFLP) [10]. IVDMD was ranked high (>62%), medium (55-62%), or low (<55%).…”
Section: Methodsmentioning
confidence: 99%
“…Fifty entries with the widest range in rumen digestibility and fiber were selected for the current study (Table 1). The Table 1 Bermuda grass entries and their ranking for high (H), medium (M), or low (L) levels of IVDMD, NDF, ADF, ADL from previous screening, leaf/stem coarseness, and genetic clustering from breeder plots and the Bermuda grass core collection grown at Tifton, GA molecular genetic relationship between these entries was documented using amplified fragment-length polymorphisms (AFLP) [10]. IVDMD was ranked high (>62%), medium (55-62%), or low (<55%).…”
Section: Methodsmentioning
confidence: 99%
“…Previous population structure analyses of the international collection have also found that species did not form discrete clusters. This was reportedly due to mis-naming of accessions prior to Harlan et al's (1970) revision of the genus, contamination among nursery plots since establishment of the collection in the 1940's, and taxonomic confusion during species classification (Anderson et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction procedures and EST-SSR analyses have been reported previously (Jewell et al 2010;Kearns et al 2009;Zhou et al 2009). DNA from 59 international accessions representing global distribution was provided by the USDA-ARS in Tifton, GA (international collection; IC; Anderson et al 2009). These accessions were a subset of a core collection of 600 accessions maintained at the Crop Genetic and Breeding Research Unit (USDA-ARS Coastal Plain Experiment Station, Tifton, GA, USA).…”
Section: Plant Materials Est-ssr Genotyping and Core Collection Devementioning
confidence: 99%
“…Pers.) genotypes bred for high dry biomass yield produced twice as much as unimproved genotypes and recent yield trials indicated that switchgrass yields were 50% greater than those achieved in early 2000 [293]. Therefore, instant determination of net energy value is a valuable tool for plant breeders and growers to tailor genotypic development, hybrid selection, and crop management to produce the highest dry biomass yield [288].…”
Section: Genetics Breeding Transgenics and Carbon Sequestrationmentioning
confidence: 99%
“…Therefore, the cereal ideotype was phenotypically characterized by a short stem, small erect leaves, a low number of tillers, and a large and awned ear. As yield is a property of a population of plants and is poorly correlated with the performance of an individual plant in the population [118,183,245,251,293], the cereal crop ideotype was designed to be a weak competitor to reduce intra-crop interference and thereby maximize yield per unit area. Advancing appropriate genetic models for bioenergy crops is indispensable in the development of agroecosystem approaches to improve several traits related to dry biomass yield and bioenergy production, and to enhance global climate change adaptation and mitigation.…”
Section: Genetic Models and Ideotypes Of Bioenergy Cropsmentioning
confidence: 99%